Prevalence of Polycystic Ovarian Disease in Zawia Medical Center - Ibtisam Khapoli; Hager Elwani; Abdeulmajid Khapoli; Karima Dabob; Naseba Khapoli (AlQalam Journal of Medical and Applied Sciences, 2025)
Polycystic Ovary Syndrome (PCOS) is a prevalent endocrine disorder affecting women of reproductive age, leading to various metabolic, hormonal, and reproductive health complications. This study aimed to evaluate the prevalence and demographic characteristics of PCOS in Zawia, Libya, among women aged 18–45 years. A descriptive, cross-sectional survey was conducted at Zawia Medical Center (ZMC) from March to May 2024, involving 200 women diagnosed with PCOS and 500 controls. The Rotterdam criteria were used for diagnosis, with participants completing questionnaires on demographics, symptoms, and family history. The prevalence of PCOS was found to be 28.5%, with most patients aged 18-29 years (71.5%). Common symptoms included weight gain (87.5%), hirsutism (82%), and irregular periods (82%), and a significant proportion of patients (56%) reported a family history of PCOS. Obesity was prevalent, with 76% of patients classified as obese. The findings underscore the need for early diagnosis, awareness, and targeted interventions to manage PCOS and reduce its associated health risks. The study highlights the significance of genetic factors and emphasizes a comprehensive approach to treatment that includes lifestyle modifications, education, and counseling to improve the quality of life for women affected by PCOS in Libya. متلازمة المبايض المتعددة الكيسات هي اضطراب هرموني شائع يؤثر على النساء في سن الإنجاب، مما يؤدي إلى العديد من المضاعفات الصحية المتعلقة بالتمثيل الغذائي، والهرمونات، والصحة الإنجابية. تهدف هذه الدراسة إلى تقييم انتشار وخصائص متلازمة المبايض المتعددة الكيسات في مدينة الزاوية، ليبيا، بين النساء اللواتي تتراوح أعمارهن بين 18 و45 عامًا. تم إجراء مسح وصفي عبر مقطعي في مركز الزاوية الطبي من مارس إلى مايو 2024، شمل 200 امرأة تم تشخيصهن بمتلازمة المبايض المتعددة الكيسات و500 حالة ضابطة. تم استخدام معايير روتردام للتشخيص، حيث أكمل المشاركون استبيانات حول الخصائص الديموغرافية والأعراض والتاريخ العائلي. تبين أن انتشار متلازمة المبايض المتعددة الكيسات كان 28.5%، حيث كانت الغالبية العظمى من المرضى تتراوح أعمارهن بين 18-29 سنة (71.5%). كانت الأعراض الشائعة تشمل زيادة الوزن (87.5%)، الشعرانية (82%)، وعدم انتظام الدورة الشهرية (82%)، وأفاد نسبة كبيرة من المرضى (56%) بوجود تاريخ عائلي للإصابة بالمتلازمة. كانت السمنة شائعة حيث تم تصنيف 76% من المرضى على أنهم يعانون من السمنة. تؤكد النتائج على أهمية التشخيص المبكر، وزيادة الوعي، والتدخلات المستهدفة لإدارة متلازمة المبايض المتعددة الكيسات وتقليل المخاطر الصحية المرتبطة بها. تسلط الدراسة الضوء على أهمية العوامل الوراثية وتؤكد على ضرورة اتباع نهج شامل في العلاج يشمل تعديلات نمط الحياة، والتعليم، والإرشاد لتحسين جودة الحياة للنساء المصابات بمتلازمة المبايض المتعددة الكيسات في ليبيا